ECE Educator Performance: Teaching Experience and Peer Teaching Ability through Basic Tiered Training - Soffianningrum, Imbarsari; Yufiarti; Yetti, Elindra (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
ABSTRACT: Teacher performance has been the focus of educational policy reforms in recent decades for the professional development of teachers. The purpose of this study was to determine the effect of teaching experience and peer teaching skills on basic training on ECE teacher performance. This research uses ex-post facto quantitative method of comparative analysis and design by level. The population is all ECE teachers who attend basic-level education and training in Tangerang Regency, totaling 3358 people consisting of 116 male teachers and 3,242 female teachers. Data collection techniques using a questionnaire with data analysis include descriptive analysis. Requirements test analysis and inferential analysis. The results show that there are differences in the performance of ECE teachers between teachers with more than five years of teaching experience and less than five years, in the group of ECE teachers with high peer teaching skills and low peer teaching skills. The implication of this research is that it is hoped that various parties will become more active in aligning ECE teacher training so that it can improve the performance of ECE teachers. Keywords: teaching experience, peer teaching ability, tiered basic training, ECE teacher performance References: Adeyemi, T. (2008). Influence of Teachers’ Teaching Experience on Students’ Learning Outcomes in Secondary Schools in Ondo State, Nigeria. African Journal of Educational Studies in Mathematics and Sciences, 5(1), 9–19. https://doi.org/10.4314/ajesms.v5i1.38609 Ahmad, N. J., Ishak, N. A., Samsudin, M. A., Meylani, V., & Said, H. M. (2019). Pre-service science teachers in international teaching practicum: Reflection of the experience. Jurnal Pendidikan IPA Indonesia, 8(3), 308–316. https://doi.org/10.15294/jpii.v8i3.18907 Andrin, G. R., Etcuban, J. O., Watin, A. K. O., Maluya, R., Rocha, E. D. V, & Maulit, A. A. (2017). Professional Preparation and Performance of Preschool Teachers in the Public and Private Schools of Cebu City, Philippines. ACADEME, 10. Andrin, Glenn R, Etcuban, J. O., Watin, A. K. O., Maluya, R., Rocha, E. D. V, & Maulit, A. A. (2017). Professional Preparation and Performance of Preschool Teachers in the Public and Private Schools of Cebu City, Philippines. ACADEME, 10. Armytage, P. (2018). Review of the Victorian Institute of Teaching. Bichi, A. A. (2019). Evaluation of Teacher Performance in Schools: Implication for Sustainable Evaluation of Teacher Performance in Schools: Implication for Sustainable Development Goals. December 2017. Campolo, M., Maritz, C. A., Thielman, G., & Packel, L. (2013). An Evaluation of Peer Teaching Across the Curriculum: Student Perspectives. International Journal of Therapies and Rehabilitation Research, 2(1), 1. https://doi.org/10.5455/ijtrr.00000016 Clearinghouse, W. W. (2018). National Board for Professional Teaching Standards Certification. Colthart, I., Bagnall, G., Evans, A., Allbutt, H., Haig, A., Illing, J., & McKinstry, B. (2008). The effectiveness of self-assessment on the identification of learner needs, learner activity, and impact on clinical practice: BEME Guide no. 10. Medical Teacher, 30(2), 124–145. Darling-Hammond, L. (2011). Teacher quality and student achievement. Teacher Quality and Student Achievement, 8(1), 1–215. https://doi.org/10.14507/epaa.v8n1.2000 Donaldson, M. L. (2009). So long, Lake Wobegon? Using teacher evaluation to raise teacher quality. Center for American Progress, 1–32. Fogaça, N., Rego, M. C. B., Melo, M. C. C., Armond, L. P., & Coelho, F. A. (2018). Job Performance Analysis: Scientific Studies in the Main Journals of Management and Psychology from 2006 to 2015. Performance Improvement Quarterly, 30(4), 231–247. https://doi.org/10.1002/piq.21248 Frye, E. M., Trathen, W., & Koppenhaver, D. A. (2010). Internet workshop and blog publishing: Meeting student (and teacher) learning needs to achieve best practice in the twenty-first-century social studies classroom. The Social Studies, 101(2), 46–53. Hanushek, E. A. (2011). The economic value of higher teacher quality. Economics of Education Review, 30(3), 466–479. Heryati, Y., & Rusdiana, A. (2015). Pendidikan Profesi Keguruan. Bandung: CV Pustaka Setia. John P. Papay Eric S. Taylor John H. Tyler Mary Laski. (2016). Learning Job Skills From Colleagues At Work: Evidence From A Field Experiment Using Teacher Performance Data (p. 49). Katz, L. G., & Raths, J. D. (1985). Dispositions as goals for teacher education. Teaching and Teacher Education, 1(4), 301–307. Kavanoz, S., & Yüksel, G. (2015). An Investigation of Peer-Teaching Technique in Student Teacher Development An Investigation of Peer-Teaching Technique in Student Teacher Development. June 2010. Kurniawan, A. R., Chan, F., Sargandi, M., Yolanda, S., Karomah, R., Setianingtyas, W., & Irani, S. (2019). Kebijakan Sekolah Dalam Penggunaan Gadget di Sekolah Dasar. Jurnal Tunas Pendidikan, 2(1), 72–81. Lim, L. L. (2014). A case study on peer-teaching. Open Journal of Social Sciences, 2(08), 35. Manchishi, P. C., & Mwanza, D. S. (2016). Teacher Preparation at the University of Zambia: Is Peer Teaching Still a Useful Strategy? International Journal of Humanities, Social Sciences and Education, 3(11), 88–100. https://doi.org/10.20431/2349-0381.0311012 Mansur, M. (2007). KTSP: Pembelajaran Berbasis Kompetensi dan Kontekstual, Jakarta: PT. Bumi. Marais, P., & Meier, C. (2004). Hear our voices: Student teachers’ experiences during practical teaching. Africa Education Review, 1(2), 220–233. https://doi.org/10.1080/18146620408566281 McFarland, J., Hussar, B., Wang, X., Zhang, J., Wang, K., Rathbun, A., Barmer, A., Cataldi, E. F., & Mann, F. B. (2018). The Condition of Education 2018. NCES 2018-144. National Center for Education Statistics. Meilanie, R. S. M., & Syamsiatin, E. (2020). Multi Perspectives on Play Based Curriculum Quality Standards in the Center Learning Model. Jurnal Pendidikan Usia Dini, 14(1), 15–31. Michael Luna, S. (2016). (Re)defining “good teaching”: Teacher performance assessments and critical race theory in early childhood teacher education. Contemporary Issues in Early Childhood, 17(4), 442–446. https://doi.org/10.1177/1463949116677932 Morgan, G. B., Hodge, K. J., Trepinski, T. M., & Anderson, L. W. (2014). The Stability of Teacher Performance and Effectiveness: Implications for Policies Concerning Teacher Evaluation Grant. Mulyasa, E. (2013). Uji kompetensi dan Penilaian Kinerja guru. Bandung: PT Remaja Rosdakarya. Nasrun, Dr., & Ambarita, D. F. P. (2017). The Effect of Organizational Culture and Work Motivation on Teachers Performance of Public Senior High School in Tebing Tinggi. Atlantis Press, 118, 320–326. https://doi.org/10.2991/icset-17.2017.53 Nguyen, M. (2013). Peer tutoring as a strategy to promote academic success. Research Brief. Noelke, C., & Horn, D. (2010). OECD Review on Evaluation and Assessment Frameworks for Improving School Outcomes-Hungary Country Background Report. OECD: PARIS. OECD. (2005). Teacher’s matter. Attracting, developing, and retaining effective teachers. Paris. OECD-Education Committee. Pablo Fraser, Gabor Fülöp, M. L. and M. S. D. (2018). I.  What teachers and school leaders say about their jobs. TALIS, 2, 1–7. Parihar, K. S., Campus, D., Principal, J., & Campus, D. (2017). Study Of Effect Of Pre Teaching Training Experience On. 5, 59–62. https://doi.org/10.5281/zenodo.1039595 Parsons, S. A., Vaughn, M., Scales, R. Q., Gallagher, M. A., Parsons, A. W., Davis, S. G., Pierczynski, M., & Allen, M. (2018). Teachers’ instructional adaptations: A research synthesis. Review of Educational Research, 88(2), 205–242. Pillay, R., & Laeequddin, M. (2019). Peer teaching: A pedagogic method for higher education. International Journal of Innovative Technology and Exploring Engineering, 9(1), 2907–2913. https://doi.org/10.35940/ijitee.A9106.119119 Popova, A., Evans, D. K., & Arancibia, V. (2018). Training Teachers on the Job What Works and How to Measure It. Policy Research Working Paper, September 2016. Ramadoni, W., Kusmintardjo, K., & Arifin, I. (2016). Kepemimpinan Kepala Sekolah dalam Upaya Peningkatan Kinerja Guru (Studi Multi Kasus di Paud Islam Sabilillah dan Sdn Tanjungsari 1 Kabupaten Sidoarjo). Jurnal Pendidikan: Teori, Penelitian, Dan Pengembangan, 1(8), 1500–1504. Rees, E. L., Quinn, P. J., Davies, B., & Fotheringham, V. (2016). How does peer teaching compare to faculty teaching? A systematic review and meta-analysis. Medical Teacher, 38(8), 829–837. Sawchuk, S. (2015). Teacher evaluation: An issue overview. Education Week, 35(3), 1–6. Skourdoumbis, A. (2018). Theorising teacher performance dispositions in an age of audit. 1–16. https://doi.org/10.1002/berj.3492 Springer, M. G., Swain, W. A., & Rodriguez, L. A. (2016). Effective teacher retention bonuses: Evidence from Tennessee. Educational Evaluation and Policy Analysis, 38(2), 199–221. Staiger, D. O., & Rockoff, J. E. (2010). Searching for effective teachers with imperfect information. Journal of Economic Perspectives, 24(3), 97–118. Suyatno, H., & Pd, M. (2008). Panduan sertifikasi guru. Jakarta: PT Macanan Jaya Cemerlang. ten Cate, O. (2017). Practice Report / Bericht aus der Praxis: Peer teaching: From method to philosophy. Zeitschrift Fur Evidenz, Fortbildung Und Qualitat Im Gesundheitswesen, 127–128, 85–87. https://doi.org/10.1016/j.zefq.2017.10.005 Thurlings, M., & den Brok, P. (2018). Student teachers’ and in-service teachers’ peer learning: A realist synthesis. Educational Research and Evaluation, 24(1–2), 13–50. https://doi.org/10.1080/13803611.2018.1509719 Toch, T., & Rothman, R. (2008). Rush to Judgment: Teacher Evaluation in Public Education. Education Sector Reports. Education Sector. Ünal, Z., & Unal, A. (2012). The Impact of Years of Teaching Experience on the Classroom Management Approaches of Elementary School Teachers. International Journal of Instruction, 5(2), 41–60. Vasay, E. T. (2010). The effects of peer teaching in the performance of students in mathematics. E-International Scientific Research Journal, 2(2), 161–171. Weisberg, D., Sexton, S., Mulhern, J., Keeling, D., Schunck, J., Palcisco, A., & Morgan, K. (2009). The widget effect: Our national failure to acknowledge and act on differences in teacher effectiveness. New Teacher Project. Winters, M. A., & Cowen, J. M. (2013). Would a value‐added system of retention improve the distribution of teacher quality? A Simulation of Alternative Policies. Journal of Policy Analysis and Management, 32(3), 634–654.